PENGARUH STRATEGI PELAYANAN TERHADAP PENINGKATAN KEPUASAN PELANGGAN PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) DI BATURAJA - Santi Puspita; Fikri Kurniawan (STIE DWI SAKTI BATURAJA, 2022)
The purpose of this study was to determine the effect of service strategy on increasing customer satisfaction at the regional drinking water company (PDAM) in Baturaja. The research method used is descriptive method with qualitative and quantitative data analysis techniques, the measuring tools used are validity test, reliability test, simple linear regression analysis, correlation coefficient analysis (r), coefficient of determination (KD) and hypothesis testing (t test). The results of this study reveal that there is an influence of service strategy on increasing customer satisfaction at the regional drinking water company (PDAM) in Baturaja. Based on the results of data analysis that has been carried out with the results of simple linear regression Y = 2.973 + 0.871 X, from this equation it can be seen that the coefficient is positive, meaning that there is a positive relationship between service strategy and customer satisfaction. The results of the analysis of the coefficient of determination or R Square is 0.682 or 68.2%. This shows that customer satisfaction (Y) is influenced by 68.2% by service strategy (X), while the remaining 31.8% is influenced by other variables not examined in this study